Reflective smartphone disengagement: Conceptualization, measurement, and validation - Matthes, Jörg; Karsay, Kathrin; Hirsch, Melanie; Stevic, Anja; Schmuck, Desirée (Computers in human behavior, 2022)
The present paper develops a new concept, called Reflective Smartphone Disengagement (RSD), defined as individuals’ deliberate efforts to control and restrict smartphone use. Based on the reflective-impulsive model, we examined the RSD concept in four studies, using cross-sectional data of adolescents (Study 1, N = 453, Study 3, N = 760) and adults (Study 4, N = 672), as well as panel data of adults (Study 2, N = 461). In Study 1, findings from exploratory and confirmatory factor analyses supported the one-dimensionality of the RSD scale. In Study 2, we found evidence for high test–retest reliability as well as discriminant validity, and in terms of predictive validity, RSD negatively predicted excessive smartphone use, information overload, and the social availability norm over time. Study 3 demonstrated convergent validity with a negative relationship with trait nomophobia and a positive one with trait self-reflection. Study 4 confirms the structural validity of a shorter version of the scale. We discuss avenues for future research and broader implications of the RSD concept for the field. •We develop the Reflective Smartphone Disengagement (RSD) scale.•RSD is defined as deliberate efforts to restrict and control smartphone use.•There is evidence for structural, predictive, discriminant, and convergent validity.•RSD negatively relates to excessive use, information overload and social availability norm.•RSD is negatively related to nomophobia and positively to self-reflection.